Geographical indications: The economics of claw-back - Daniela Benavente (Graduate Institute of International and Development Studies, 2010)
Geographical Indications (GIs) for products (Basmati rice, Champagne sparkling wine, Antigua coffee, etc.) were regulated at the international level in 1995 (WTO TRIPS Agreement, Part II, Section 3). This paper proposes a model on the welfare effects of the socalled claw-back of GIs; i.e. the protection in a country (Home) of a GI of another country (Foreign), when the said GI had previously acquired generic status at Home (cf.: protection of Feta in the EU or of Champagne in Chile). The setting includes two countries (Home and Foreign); three varieties (Foreign GI-original goods, Home GI-variety goods and generics) and a continuum of heterogeneous consumers. Two regimes are analyzed: protection/no protection; in two scenarios for Foreign firms: perfect/oligopolistic competition. Only the equilibrium at Home is analyzed. Although a loss in global welfare is always expected when fewer varieties are available in a market, results suggest that industrialized Home countries, with sophisticated consumers and higher relative costs tend to lose less from protecting Foreign GIs than developing Home countries, where the opposite is true. With oligopolistic competition, GI firms become from differentiated from their closest competitor after protection (now generics), further stressing the competitive distortion; consumers with a low willingness to pay for origin and a high degree of valuation for the GI-variety are the biggest losers. Regarding firms, however, contrary to the conventional wisdom, oligopolistic competition by Foreign firms leads to less stringent conditions for Home GI-varieties to compete, and does not affect generics. In effect, if after protection Home GI-varieties can successfully differentiate themselves from Foreign GI-original goods without the (unlawful) use of the GI label (either through the development of their own GI or through proper branding) and stay competitive, the scenario of oligopolistic competition from Foreign firms is more favorable to their development than the scenario of perfect competition.
Keywords: 330; Herkunftsbezeichnung; Wohlfahrtsanalyse; Zwei-Länder-Modell; Theorie